Analisis Pengetahuan Penggunaan Obat Paten dan Obat Generik di Desa Sukorejo Kecamatan Ulujami Kabupaten Pemalang - Amanda Dwijayanti; Musa Fitri Fatkhiyah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Patented drugs are a type of drug that has just been discovered and has a certain patent period based on its type. This drug is designed to provide convenience through innovations such as practical packaging, better taste, and syrup that is not bitter due to the use of micro particles. Technologies such as slow-release tablets or sugar coatings also reduce side effects in the stomach, making them safer to use. In addition, this innovation can overcome other obstacles, such as avoiding alcohol solvents that are not in accordance with some religious beliefs. On the other hand, generic drugs still meet pharmacopoeial requirements and have gone through a good drug manufacturing process (CPOB), with strict supervision from the Food and Drug Supervisory Agency (BPOM). This study aims to determine the level of knowledge of the people of Sukorejo Village about patented and generic drugs. The type of research used is descriptive, using a questionnaire as a data collection tool. The sample consisted of 100 people selected through a simple random sampling technique, where each element of the population has an equal chance of being selected. Percentage analysis was used to evaluate the results of the study. The data shows that 49% of respondents have good knowledge of patented and generic drugs, while 23% have sufficient knowledge. These results indicate that the majority of the community already understands the differences between the two types of drugs.